Poverty risk and quality of housing in the EU regions with a different urbanisation rate - Kraftová, Ivana; Provazníková, Romana; Korovchenko, Tetiana (My University, 2020)
The aim of this article is to compare selected parameters of quality of life in the European Union countries by the degree of urbanization of living space and to verify the validity of three hypotheses aimed at quality of life evaluation in rural EU areas. The main data source is the Eurostat statistical data. Comparative analysis, variability, and concentration analysis using the method of adjusted index of geographical concentration have been applied during the processing. The analysis results show that the degree of risk of poverty "is split" in the EU between rural areas and cities. In this respect, European countries are divided into two roughly equal groups. The degree of concentration of people at risk of poverty in rural areas exceeds half the attainable interval. The extent of the actual geographic concentration of the population, and at the same time the disparities existing between European countries are both involved in it. Cost and quality of housing show the highest variability within European rural areas. The findings are in accordance with those experts who plead for a more effective tool targeting of EU cohesion policy in pursuit of its objectives in the field of poverty decreasement.
Ohrožení chudobou a kvalita bydlení v regionech EU s odlišnou mírou urbanizace
Keywords: rural region; housing; degree of urbanization; risk of poverty; overcrowding; cost overburden; venkovské regiony; bydlení; míra urbanizace; ohrožení chudobou; přelidněné obydlí; nákladové přetížení